QUALITY IMPROVEMENT IN FOOTWEAR SME USING THE DMAIC METHOD OF SIX SIGMA - Susanti, Haniatu; Helia, Vembri Noor (Universitas Islam Nahdlatul Ulama Jepara, 2025)
Quality control through systematic analysis and preventive measures is essential to minimize product nonconformities. This study aims to identify the number of defects in men's pantofel shoes, calculate the Defects Per Million Opportunities (DPMO), and determine the sigma level of the production process. One effective method for quality control is Six Sigma, which targets significant quality improvements by aiming for zero defects. The Six Sigma approach applied in this study follows the DMAIC methodology (Define, Measure, Analyze, Improve, and Control). The research was conducted on a footwear SME, and the identified category of defects is attribute defects. Attribute defects involved issues such as glue stains, loose insoles, uneven stitching, and torn leather. Out of 1,050 observed samples, 155 units (14.76%) were found to be defective, with glue stain defects accounting for the majority (92 units or 59%). The DPMO for attribute data was calculated at 36,904.8, corresponding to a sigma level of 3.28. Based on the findings, recommendations are proposed to reduce the occurrence of glue stain defects as a priority for quality improvement. The predominant cause of glue stain defects is insufficient lighting at the gluing workstation. Therefore, the proposed improvement focuses on enhancing lighting conditions, formulated using the 5W+1H method.PENINGKATAN KUALITAS DI UKM SEPATU MENGGUNAKAN METODE SIX SIGMA DMAICPengendalian kualitas melalui analisis sistematis dan tindakan pencegahan sangat penting untuk meminimalkan ketidaksesuaian produk. Penelitian ini bertujuan untuk mengidentifikasi jumlah cacat pada sepatu pantofel pria, menghitung nilai Defects Per Million Opportunities (DPMO), serta menentukan level sigma dari proses produksi. Salah satu metode pengendalian kualitas yang efektif adalah Six Sigma, yang bertujuan untuk meningkatkan kualitas secara signifikan hingga mendekati zero defect. Pendekatan Six Sigma dalam penelitian ini diterapkan melalui metodologi DMAIC (Define, Measure, Analyze, Improve, dan Control). Penelitian dilakukan pada sebuah UKM sepatu dan mengidentifikasi kategori cacat, yaitu cacat atribut. Sementara itu, cacat atribut mencakup noda lem, sol yang tidak merekat, jahitan yang kurang rapi, dan kulit yang robek. Dari 1.050 sampel yang diamati, ditemukan 155 unit (14,76%) mengalami cacat, dengan cacat berupa noda lem mendominasi (92 unit atau 59%). Nilai DPMO untuk data atribut dihitung sebesar 36.904,8, yang setara dengan level sigma sebesar 3,28. Berdasarkan temuan tersebut, direkomendasikan upaya perbaikan yang difokuskan pada pengurangan risiko cacat berupa noda lem sebagai prioritas peningkatan kualitas. Penyebab dominan cacat noda lem berasal dari faktor kurangnya pencahayaan pada stasiun kerja proses pengeleman. Oleh karena itu, usulan perbaikan difokuskan pada peningkatan pencahayaan menggunakan metode 5W+1H.